Preparation and characterization of protein isolate and biodiesel from garden cress seed - Ali, Rehab Farouk Mohammed (European Journal of Chemistry, 2013)
Garden cress seeds were analyzed for proximate composition and mineral content. The protein isolate (PI) was evaluated for chemical composition, mineral content, amino acid composition, biological values and some functional properties. The seed oil was evaluated for fatty acid profile; tocopherols and some of physicochemical properties were studied. Seeds were found to contain 29.11% oil and 25.12% protein. Phosphorus, magnesium and calcium constituted the major minerals of the seeds. The protein efficiency ratio (PER) of PI was 2.37. PI was found to possess relatively high values of water and fat absorption capacity, emulsification capacity and foam capacity. The fatty acid profile showed that linolenic acid (41.17%) and oleic acid (26.42%) were the major unsaturated fatty acids, whereas palmitic acid was the major saturated acid. Total tocopherol content of garden cress oil was 150.46 mg/100 g oil. The physicochemical characteristics of oil and biodiesel meet the norm specifications.